Intervention mapping for systematic development of a community-engaged CVD prevention intervention in ethnic and racial sexual minority men with HIV - Kang, Baram; Chin, Lauren; Camacho-Rivera, Marlene; Garza, Michael; de Jesús Espinosa, Tania; Cong, Xiaomei; Fraser, Marilyn; Boutjdir, Mohamed; Ramos, S. Raquel (Frontiers in Public Health, 2025)
IntroductionCardiovascular disease (CVD) is a leading cause of mortality in the United States, disproportionately affecting marginalized populations such as Black and Latinx sexual minority men with HIV. These individuals face heightened CVD risk due to chronic inflammation related to HIV, side effects from treatment, and intersecting social disadvantages, including stigma and discrimination. Behavioral interventions specifically targeting these populations have been limited, with insufficient uptake in marginalized communities.MethodsThis study used Intervention Mapping (IM) to develop a culturally tailored CVD prevention intervention for Black and Latinx sexual minority men with HIV. IM is a systematic, theory- and evidence-based framework for health promotion program planning. We focused on the first three of six steps in the IM process: (1) assessing community needs through literature review, framework development, and community-engaged research; (2) identifying program outcomes to develop a logic model of change; and (3) selecting theory-based methods and practical strategies for program design.ResultsThe needs assessment revealed significant barriers to cardiovascular health, including medical distrust, stigma, and lack of access to culturally appropriate healthcare. The logic model of change highlighted behavioral and environmental determinants influencing cardiovascular health, leading to specific performance objectives and change objectives. Strategies included leveraging eHealth technologies, such as avatar-led interactive videos, to provide private, culturally relevant health education and reduce barriers like medical distrust. Community-based participatory methods were integral to ensure the intervention was culturally resonant and acceptable.DiscussionThis study demonstrated the use of IM to systematically develop a culturally tailored CVD prevention intervention for Black and Latinx sexual minority men with HIV. The findings highlight the importance of community-engaged and culturally appropriate approaches in developing interventions for historically marginalized populations. These strategies aimed to address health disparities and empower them to engage in cardiovascular health-promoting behaviors, ultimately improving cardiovascular health outcomes. Leveraging technology to foster engagement and providing culturally relevant support were crucial elements of the intervention. The insights gained may inform future cardiovascular health promotion efforts targeting similar populations.